INJECTIVE STRUCTURES AND GOLD-SILVER MINERALIZATION OF THE POKROVSK ORE FIELD (AMUR REGION, RUSSIA) - Khomich V.G.; Boriskina N.G. (My University, 2003)
It is shown that the formation of the Pokrovsk ore field structure is related to injective processes that occurred repeatedly in the Umlekan-Ogodzha volcano-plutonic belt during the Late Mesozoic. This is confirmed by the occurrence of the Sergeevsk hypabyssal granodiorite-granite massif (Verkhneamursk complex, J 3-K 1), linear granosyenite fracture intrusions and large magnophyric granite dikes (Magdagacha complex, J 3-K 1), andesite, spessartite, microdiorite, and monzodiorite dikes (Burinda complex, K 1), subvolcanic dacite-granodiorite-porphyry bodies, and their volcanic analogues (Kerak complex, K 1). The local paleochimney, about 600 m across, filled in with the Kerak granodiorite-porphyries, and surrounded by volcanic and moderately acid pyroclastic rocks up to 50-250 m thick represents the main structural element of the ore field in question. Epithermal gold-silver mineralization (Au/Ag = 1/2-3) is observed in several areas that are located along the periphery of paleochimneys, two of which enclose commercial gold ores that are developed by open mining. In the Pokrovka-I area, stockwork-shaped lodes occur in granitoids of the Verkhneamursk complex, whereas, in the Pokrovka-III area, they are enclosed in effusive-pyroclastic rocks of the Kerak suite. The mineralization in the Pokrovka-I area is confined to the lenticular granitoid body of a variable thickness (0 to 200 m). The ore-enclosing body is overlain by a sequence of metasomatically altered volcanics and underlain by a thick dacite-granodiorite-porphyry sill. The detailed deep-level mapping in the central part of the Pokrovskoe ore field (using core samples from hundreds of boreholes, logging data, and special maps) revealed factors responsible for the distribution of gold-silver mineralization. Basic among them are injective elements and structures, whose formation is related to intrusion of magma into substrate rocks: concealed dome-shaped uplift formed by a thick dacite-granodiorite-porphyry sill and synforms complicating the dome structure, as well as areas with a sharp thickness change and pinching of the sill and lenticular ore-enclosing Sergeevsk granitoid massif. The obvious spatial relation of the ore-enclosing lodes (Pokrovka-I area) to dacite-granodiorite-porphyry sill and concealed dome of the injective origin, as well as the distribution of gold-silver mineralization (Pokrovka-III area) within the Kerak volcanics, give grounds to consider the Kerak igneous rocks as both ore-hosting and ore-bearing.